Numerical investigation of flow over obstacles on a backward-facing step - Bayraktar, Seyfettin (GAZI UNIV, FAC ENGINEERING ARCHITECTURE, 2021)
In the present study, the effects of the square, circular and equilateral triangular cross-sectional obstacles placed on a backward-facing step on the flow-field were investigated numerically. Assumed to be fully turbulent, three-dimensional, steady and incompressible flow was solved by modified k-omega turbulence model. Obtained results were exhibited in terms of non-dimensional friction and non-dimensional pressure coefficients in addition to non-dimensional reattachment length. Apart from the geometric shapes of the obstacles, the influence of their heights (h) on the relevant parameters were presented for H/h=0.125, 0.25, 0.5 and 1 by dimensionalizing with the step height (H). Results obtained for the backward-facing step without any obstacles were compared with the experimental data of Driver and Seegmiller, 1985 to show the accuracy of the model. It was shown that in comparison with the step without the obstacles, not only the existence of the obstacles but their cross-sectional shapes also affect friction and pressure coefficients and the reattachment length. Regardless of the cross-sectional geometry of the obstacles, it was detected that the existence of the obstacles increases the length of the recirculation, however, the longest regions were obtained when equilateral triangular cross-sectional one was used. It was revealed that the effect of the height of the obstacle on the detached flow region is quite low for H/h=0.25.
Keywords: Backward-facing step; Separation; Turbulence; Recirculation; Obstacle; HEAT-TRANSFER CHARACTERISTICS; REYNOLDS-NUMBER; FORCED-CONVECTION; OMEGA; ADJACENT; CHANNEL; MODELS; LAYER; Engineering